Parental Involvement in Education Among Albanian Parents - Thartori, Voltisa (IIUM Journal of Educational Studies, 2019)
Parents' involvement has a huge influence on children’s educational engagement during the elementary years, the study sought to examine the perceptions of Albanian parents of their involvement in their children's schooling at the Qemal Stafa School in Albania. The parental involvement construct examined in the study was conceptualized based on Epstein’s (1995) six categories of parental involvement comprising parenting, communicating, volunteering, learning at home, decision-making, and collaborating with the community. The data collected through the questionnaire were analyzed using descriptive statistics, Pearson correlation and ANOVA. The results showed a high level of parental involvement in the Albanian children’s learning development. The parents surveyed reported volunteering in many workshops that the school conducted. In addition, the results indicated that some parents maintained a good communication with teachers. The ANOVA results showed statistically significant differences in parental involvement by age, marital status, education level, Income Level. Variables such as communicating, and volunteering were identified as the most important components of parental involvement.